The Psychological Impact of Smog Pollution on Investors - Li, Bin; Liu, Yang; Zhang, Tingyu; Wang, Yijing (Frontiers in Psychology, 2022)
This research empirically analyzes the psychological impact of smog pollution on investors. Results indicate that smog pollution has negative impact on investor sentiment which is weakened by the positive tone in media reporting. Empirical evidence for the impact of smog pollution on investor sentiment and the related moderating role of media tone is presented in this study.